Far-Infrared Absorption in Insb - Koteles, Emil Steve (My University, 1973)
A high-resolution, low-noise far-infrared Fourier transform spectrometer system has been developed and utilized to study optical absorption in the III-V compound semiconductor InSb.
Its electron effective mass was investigated, using cyclotron resonance absorption, as a function of magnetic field and compared with a theory originated by Kane (1957). The agreement was good and accurate values of the band edge effective mass and effective g factors were determined. Resonant electron-LO phonon coupling between the n = 2 and n = 0 + wLO Landau levels was observed and the polaron effective mass enhancement measured as a function of magnetic field. Comparison with Larsen's theory (1966), permitted an accurate value of the coupling constant to be derived. The temperature dependence of the electron effective mass was shown to be primarily due to dilation of the crystal lattice in confirmation of other workers' suggestions. However, some discrepancy, whose origin is unknown, was found to exist between experiment and theory.
Single phonon absorption by the longitudinal optic phonon mode at the zone center was observed on the side of the main Reststrahl band in a thin sample. The shapes, frequencies and intensities of far-infrared absorptions attributable to two-phonon processes were found to compare favourably with a theoretical two-phonon density of states curve calculated by G. Dolling (1972). The parameters used in the theory were derived from inelastic neutron scattering experiments. Two phonon combinations and their locations in the Brillouin zone which give rise to strong features in the two-phonon density of states were identified by comparing theory and experiment. Important critical points were discovered to be located on or near the zone boundary and not only at the symmetry points X and L as previously suggested. The frequency shifts of some two-phonon features were measured as a function of temperature and analyzed in terms of a quasi-harmonic lattice dilation component and an anharmonic component. The two terms were found to be mirror images as a function of temperature.
Keywords: far-infrared, absorption, semiconductor, electron, magnetic, field, crystal lattice, harmonic